Vertigo - Hitchcock, Alfred, 1899-1980; Coppel, Alec; Taylor, Samuel Albert, 1912; Stewart, James, 1908-1997; Novak, Kim; Bel Geddes, Barbara; Boileau, Pierre, 1906-; Albert J. Hitchcock Productions; Paramount Pictures Corporation; Universal City Studios; LC Purchase Collection (Library of Congress); Copyright Collection (Library of Congress); et al. (United States : Paramount, 1958)
Scottie Ferguson, a San Francisco police detective is forced to retire when a freak accident gives him a severe case of acrophobia--that is vertigo or dizziness in high places. Ferguson is hired by a rich shipbuilder to follow his wife who is behaving suspiciously and might be planning suicide. He falls in love with her, she is later murdered and Ferguson becomes demonic in his desire to re-create her in another woman.
Copyright: Alfred J. Hitchcock Productions, Inc. & Paramount Pictures Corp.; 9May58; LP10837.
Parts of summary taken from The motion picture guide, vol. VIII, p. 3675 and Plain Dealer, 3/13/1984.
Two discs in one jacket.
Archival positive, copy 2, to be used as a theatrical projection print only.
LC's archival positive, copy 2, is a reissue.
Archival positive, copy 2, was selected for the National Film Registry.
Keywords: Vertigo -- Drama; Murder -- Drama; Police -- California -- San Francisco -- Drama; Love -- Drama; Features; Mysteries; Videodiscs